How To Breed Goats - Aytjanov R.T; Orinbaev B.P; Xojamuratova R.R; Menglimuratova Z.K (Global Scientific Publishing, 2024)
This article presents the trends of goat breeding, their selection, breeding and production, as well as the processes of goat breeding and breeding work.
Keywords: Down; milk; mohair; wool; goat